Europeanisation and Polish competition policy - Gwiazda, Anna (Trinity College (Dublin, Ireland). Department of Political Science, 2005)
In this thesis I analyse the impact of the European Union (EU) on domestic policies in Poland when it was a candidate country for EU membership. The impact of the European Union on domestic policies is called Europeanisation. I examined how Poland complied with EU accession criteria and responded to Europeanisation. EU membership and technical pre-accession assistance depended upon compliance with accession criteria, i.e. political, economic and acquis criteria as laid down by the Copenhagen European Council in June 1993. In particular, the acquis criterion was important as it implied the transposition of the entire Community law, called acquis communautaire, into national law.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin